2022
DOI: 10.3389/fonc.2022.903016
|View full text |Cite
|
Sign up to set email alerts
|

Present and Future Perspective on PLK1 Inhibition in Cancer Treatment

Abstract: Polo-like kinase 1 (PLK1) is the principle member of the well conserved serine/threonine kinase family. PLK1 has a key role in the progression of mitosis and recent evidence suggest its important involvement in regulating the G2/M checkpoint, in DNA damage and replication stress response, and in cell death pathways. PLK1 expression is tightly spatially and temporally regulated to ensure its nuclear activation at the late S-phase, until the peak of expression at the G2/M-phase. Recently, new roles of PLK1 have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 180 publications
1
53
0
Order By: Relevance
“…PLK1 overexpression has been observed in many types of tumors, and therefore, PLK1 has long been considered as an oncogene [ 30 ]. However, the oncogenic properties of PLK1 have not been confirmed [ 31 , 32 ]. In a study by de Cárcer et al that was published in Nature Communications, PLK1 was speculated to act as a tumor suppressor rather than as an oncogene [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLK1 overexpression has been observed in many types of tumors, and therefore, PLK1 has long been considered as an oncogene [ 30 ]. However, the oncogenic properties of PLK1 have not been confirmed [ 31 , 32 ]. In a study by de Cárcer et al that was published in Nature Communications, PLK1 was speculated to act as a tumor suppressor rather than as an oncogene [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation and ubiquitylation pathways are tightly interconnected in mitosis and it is important to understand these links in the context of carcinogenesis. PLK1 is misregulated in human cancers and small molecule inhibitors targeting PLK1 are currently being explored for cancer treatment (Chiappa et al, 2022). However, preclinical success with currently available PLK1 inhibitors has not translated well into clinical success, highlighting the need for a complete understanding of upstream PLK1 regulatory mechanisms.…”
Section: Possible Consequences Of Aberrant Plk1 Signalingmentioning
confidence: 99%
“…Protein kinases represent key regulatory elements of the mitotic cycle, transferring phosphorylation signals to critical effectors (Nigg, 2001). Polo-like kinase 1 (PLK1) represents one of the key mitotic enzymes ensuring both mitotic entry as well as fidelity of genome segregation, mitotic exit and cytokinesis (Schmucker and Sumara, 2014; Combes et al, 2017; Petronczki et al, 2008) and remains an attractive target for anticancer therapies (Chiappa et al, 2022; Strebhardt, 2010). PLK1 is a serine/threonine kinase with an enzymatic domain at its N-terminal and a Polo-Box domain (PBD) at its C-terminal part, the latter representing a unique feature of the PLK kinase family and conferring specificity to phosphorylation substrates (Strebhardt, 2010; Barr et al, 2004; Zitouni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PLK-1 inhibition, in combination with other targeted drugs such as cisplatin and paclitaxel, has thus become a new strategy for the treatment of malignant tumors. (6) This phenomenon indicates that PLK-1 is widely present in various types of tumors, suggesting that it will be a clinically valuable therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…PLK-1 is key for cell division, mitotic progression, and DNA damage repair ( 4 , 5 ). In addition, recent research has found that PLK-1 is also related to epithelial–mesenchymal transition, cell death, and the immune system ( 6 ). This protein kinase is differentially expressed in a variety of human cancers, and an increasing number of studies have shown that PLK-1 overexpression is associated with tumor progression and patient prognosis ( 7 ).…”
Section: Introductionmentioning
confidence: 99%